PEMANFAATAN SISTEM SMS GATEWAY UNTUK NOTIFIKASI IZIN TINGGAL ORANG ASING - Rezki, Muhadzib; Berlian, Theresya; Wijanarko, Ervan Fawwaaz (Polteknik Imigrasi, 2025)
This study evaluates the effectiveness of the SMS Gateway system as a notification tool for the validity period of residence permits for foreigners at an Immigration Office. With a vast operational area and challenges in monitoring, this technology is utilized to send automated notifications regarding residence permit validity. Using the System Development Life Cycle (SDLC) method, this study includes analysis, design,implementation, and evaluation to ensure the system operates optimally. The results indicate that the SMS Gateway effectively reminds foreigners about their residence permit expiration, enhancing immigration monitoring and services. The implementation of this system is expected to reduce regulatory violations and expedite the administrative process of residence permits.